Teatro do Oprimido : Deslocamento de uma Poética em Trânsito - Sousa, Renata Piona de (2016)
Replacing the Aristotelian catharsis, the piece Poetic of the Oppressed and other Political Poetics (1977) is the main ground of methodology from the Theater of the Oppressed, by Augusto Boal (1931 – 2009). His work aims to offer the means of theatrical production to the oppressed who originally suffered from class struggle, being that this production manifests itself in the whole creation process, from the dramaturgy to the staging. The perspective presented in this paper has the objective of discussing the results arisen from this process in order to verify its effects on the likely transformation of individuals oppressed by a domination logic, which is based on the brutalization and on the subtraction of the subjectivity on those who are kept away from the “common” participation, according to Jacques Ranciere. Besides relying on the French philosopher’s work, having The Politics of Aesthetics: The Distribution of the Sensible (2009) as a theoretical source, the main choices of theoretical outline will include A Thousand Plateaus - Capitalism and Schizophrenia (1995), by Deleuze and Guatarri, Culture and Imperialism (2011), by Edward Said, the works Discipline and Punish (1887) and The Discourse of Language (1996), by Michel Foucault and Critical Models: interventions and catchwords (1995), by Theodor Adorno.